The Effects of NPK fertilizer, Manure and Vesicular Arbuscular Mycorrhiza (VAM) on the Growth, Biomass and Artemisinin Content of Artemisia annua L. - Rahman, Wiguna; Widyatmoko, Didik; Lelono, Arthur A. (JURNAL BIOLOGI INDONESIA, 2014)
Most artemisinin is extracted from an annual herb Artemisia annua L. but the cultivation in Indonesia is limited bythe low yield of the artemisin incontent that is not economically beneficial to industry. Improvement on cultivatedvarieties and cultivation techniques is therefore needed. This work aims to improve the cultivation techniques byevaluating the application effects of NPK, manure, and VAM on the artemisinin yield of A. annua. The experimentwas set using a Split Split Plot Design involving three factors. First factor was the application of four dosages ofNPK (0 kg ha-1 as a control; 40:40:40 kg ha-1; 80:80:80 kg ha-1; and 120:120:120 kg ha-1). Second factor wasmanure addition (using 0 ton ha-1 and 150 tons ha-1). Third factor wasthe application of mycorrhiza (0 g plant-1and15 g plant-1). The experiment was divided into three different groups based on the seed sources (Bandung, Cibodas,and Tawangmangu plants) using similar treatments. The results showed that the plant growth (Relative GrowthRates/RGR of plant heights and number of branches), leaf yield, and total plant biomass were much affected byNPK. The addition of manure has less significant effect on those parameters. Only VAM seems to influence theartemisinin content. The highest artemisinin yield (5 kg ha-1) was relatively low when compared to the productionin USA, China, and Brazil. However the result shows that a low fertilizer input of 40:40:40 kg NPK ha-1 and aninoculation of VAM were recommended for cultivating A. annua resulting a significantly high yield of artemisinin.Keywords: Artemisia annua L., Artemisinin content, NPK, Manure, VAM, Plant Growth, Biomass